2007
DOI: 10.1002/bjs.5631
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of perioperative systemic warming in major elective abdominal surgery

Abstract: Extending systemic warming to the perioperative period had additional beneficial effects, with minimal additional cost and patient discomfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
1
15

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(126 citation statements)
references
References 28 publications
2
106
1
15
Order By: Relevance
“…Nineteen randomized controlled trials [11][12]14,18-32 on 1,785 patients qualified for this review in accordance with the inclusion criteria (Figure 1). Six trials 16,17,[33][34][35][36] were excluded for the reasons mentioned in Figure 1. The characteristics of the trials included are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen randomized controlled trials [11][12]14,18-32 on 1,785 patients qualified for this review in accordance with the inclusion criteria (Figure 1). Six trials 16,17,[33][34][35][36] were excluded for the reasons mentioned in Figure 1. The characteristics of the trials included are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The duration of perioperative warming is also under review and prolonged exposure of surgical patients to warming systems has proven to be quite effective in major elective abdominal surgery. 17 The aim of this systematic review was to compare the efficacy of perioperative warming of surgical patients aimed at reducing the consequences of wound infection, coagulopathy, blood loss, postoperative pain and postoperative shivering, in relation to no warming.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an earlier study assessing the clinical impact of extending peri-operative conductive warming during abdominal surgery has also shown that the mattresses are well tolerated and that pre-and postoperative conductive warming significantly reduces blood loss and complication rates [105].…”
Section: Resistive Heatingmentioning
confidence: 99%
“…81 In the context of colorectal surgery, warming with forced air blankets and intravenous fluids to maintain normothermia has been shown to reduce wound infection rates, 82 blood transfusion requirements, and complication rates. 83 However, there would appear to be no literature examining the impact of this strategy on the SIR following colorectal surgery. Therefore, there is no evidence that maintenance of intraoperative normothermia can reduce the surgical stress response as part of an ERAS protocol.…”
Section: Maintenance Of Intraoperative Normothermiamentioning
confidence: 99%